Systemic inflammatory response and nutritional biomarkers as predictors of nivolumab efficacy for gastric cancer - Namikawa, Tsutomu; Yokota, Keiichiro; Tanioka, Nobuhisa; Fukudome, Ian; Iwabu, Jun; Munekage, Masaya; Uemura, Sunao; Maeda, Hiromichi; Kitagawa, Hiroyuki; Kobayashi, Michiya; Hanazaki, Kazuhiro (Surgery today (Tokyo, Japan), 2020)
Purpose To investigate the usefulness of clinicopathological systemic inflammatory response and nutritional biomarkers for predicting the efficacy of nivolumab in patients with advanced gastric cancer. Methods The subjects of this study were 29 patients who received nivolumab treatment for advanced gastric cancer at the Kochi Medical School between 2017 and 2019. Clinicopathological information, including systemic inflammatory response data, were obtained to investigate the associations between baseline cancer-related prognostic variables and survival outcomes. Results Immune-related adverse events (irAEs) of any grade were identified in 34.5% (10/29) of the patients. The median progression-free survival of patients with irAEs was significantly greater than that of patients without irAEs (5.8 months vs. 1.2 months, respectively; P = 0.028). The neutrophil to lymphocyte ratio (NLR) after 4 weeks of treatment in the complete response (CR) or partial response (PR) group was significantly lower than that in the stable disease (SD) or progression disease (PD) group (2.2 vs. 2.9, respectively; P = 0.044). The prognostic nutrition index (PNI) before treatment in the CR or PR group was significantly higher than that in the SD or PD group (37.1 vs. 32.1, respectively; P = 0.011). The PNI 8 weeks after treatment and the Glasgow prognostic score (GPS) before treatment were significantly associated with a poor outcome. Conclusion The irAE, NLR, PNI, and GPS may be useful predictive markers for nivolumab efficacy in patients with advanced gastric cancer.